Determining factors for compensatory movements of the left arm and shoulder in violin playing - Margulies, Oliver; Nübling, Matthias; Verheul, William; Hildebrandt, Wulf; Hildebrandt, Horst (Frontiers in Psychology, 2023)
Despite a large number of available ergonomic aids and recommendations regarding instrument positioning, violin players at any proficiency level still display a worrying incidence of task-specific complaints of incompletely understood etiology. Compensatory movement patterns of the left upper extremity form an integral part of violin playing and are highly variable between players but remain understudied despite their relevance for task-specific health problems. This study investigated individual position effects of the instrument and pre-existing biomechanical factors likely determining the degree of typical compensatory movements in the left upper extremity: 1) left elbow/upper arm adduction (“Reference Angle α” deviation from the vertical axis), 2) shoulder elevation (“Coord x” in mm) and 3) shoulder protraction (“Coord y” in mm). In a group of healthy music students (N=30, 15m, 15f, mean age 22,5, SD 2,6), “Reference Angle α” was measured by 3D motion capture analysis. “Coord x” and “Coord y” were assessed and ranked by a synchronized 2D HD video monitoring while performing a pre-defined 16-second tune under laboratory conditions. These three primary outcome variables were compared between four typical, standardized violin positions varying by their sideward orientation (“LatAx-CSP”) and/or inclination (“LoAx-HP”) by 30°, as well as the players’ usual playing position. Selected biomechanical hand parameter data were analyzed as co-factors according to Wagner`s Biomechanical Hand Measurement (BHM). Mean “Reference Angle α” decreased significantly from 24.84±2.67 to 18,61 ±3.12 ° (p<0.001), “Coord x” from 22.54±7.417 to 4.75±3.488 mm (p<0.001), and “Coord y” from 5.66±3.287 to 1.94 ±1.901) mm (p<0.001) when increasing LatAx-CSP and LoAx-HP by 30°. Concerning the biomechanical co-factors, “Reference Angle α”, “Coord y”, but not “Coord x”, were found to be significantly increased overall with decreasing passive supination range (r=-0.307 p=<0.001 for “Passive Supination 250g/16Ncm”, and r=-0.194 p=<0.001 for “Coord y”). Compensatory movements were enlarged during tune sections requiring high positioning of the left hand and the use of the small finger. Results may enable to adapt individually suitable instrument positions to minimize strenuous and potentially unhealthy compensation movements of the left upper extremity.